Usage of Medical Library Resources: A Study in the Regional Institute of Medical Sciences, Imphal - Yashir Ahamed, MM; Lalthlamuanpuii, Ruth; Chetia, Bhagyashree; Lallawmawmi; Lalngaizuali (Indian Journal of Information Sources and Services, 2023)
This paper aims to analyse the usage of library resources, both physical and electronic, in the Central Library of the Regional Institute of Medical Sciences, Imphal. The study was designed to assess the usage of library resources in the Central Library of the Regional Institute of Medical Sciences, Imphal. The library visitor registry was surveyed for statistics. The research is limited to the usage of library resources at the RIMS’ central library during the 2016–2021 academic session. The Library has 645 members registered during the last five academic sessions. The library has a record of 13738 women and 12435 men, totalling a total of 2,6173 users who visited the library during the last 2016-2021 academic years. The highest number of visitors (1179) was recorded in September during the 2019-20 academic year, followed by (1139) in September during the 2018-19 academic year, (1127) in October, (1115) in May during the academic year 2018-19 respectively. A total of 280 users visited the print journals section of the library during the academic year 2016-17, 342 during 2017-18, 356 during 2018-19, 365 during 2019-20 and 109 during 2020-21 respectively. The library has the highest number of visitors (906) who use E-resources recorded in September followed by(827) in October during the academic year 2019-20. The least number of visitors (106) were recorded in January during the 2020-21 academic session. Further, it is found that the highest number of users (6270) visited the library during 2018-19, and only (818) during 2020-21.